Стратегія соціально-економічного розвитку вітчизняних підприємств у сучасних умовах ведення бізнесу - Новік, Ірина Олексіївна (ДВНЗ "Придніпровська державна академія будівництва та архітектури", 2019)
Стратегія соціального-економічного розвитку може розглядатися як загальний напрям дій щодо розвитку компетенцій, лояльності й ефективності роботи персоналу, необхідний підприємству для досягнення стратегічних цілей діяльності у поєднанні із задоволенням потреб і очікувань інших зацікавлених у діяльності підприємства груп: власників, споживачів, бізнес-партнерів, громадськості. У статті представлено поняття стратегії економічного й соціального розвитку як основного конструктивного елементу довгострокового планування підприємства в сучасних умовах. Визначено основні довгострокові завдання, які повинні бути вирішені в процесі розроблення і реалізації стратегії соціально-економічного розвитку підприємства. Розкрито особливості формування стратегії соціально-економічного розвитку. Запропоновано алгоритм розроблення стратегії соціально-економічного розвитку підприємства. Проаналізовано основні проблеми соціального й економічного розвитку вітчизняних підприємств. Визначено програми, які є складовими компонентами стратегії соціально-економічного розвитку сучасного підприємства.

Strategy of social – economic development can be examined as common direction of actions in relation to development of competenses, loyalty and effiiency of work of personnel, necessary to the enterprise for the achievement of strategic aims of activity in combination with satisfaction of necessities and expectations of other, groups interested in activity of enterprise : proprietors, consumers, business-partners, public. In the article the concept of strategy of economic and social development is presented as a basic structural element of the corporate strategic planning of enterprise in modern terms. Basic long-term tasks that must be decided in the process of development and realization of strategy of socio-economic development of enterprise are certain. The features of forming of strategy of socio-economic development are exposed. At modern terms a strategic management becomes necessary pre-condition of achievement of success of enterprise both on internal and on external markets, as it orients a businessman on necessities, requirements and progress of target markets trends, gives an opportunity correctly to direct activity of enterprise, assists strengthening of him competition positions and creates soil for his effective activity. In connection with it for many enterprises that carry out the activity in modern hard competition terms, the important component of strategic management are development and introduction of strategy of socio-economic development. Strategy of economic and social development is the basic structural element of the corporate strategic planning of enterprise in modern terms. Strategy must determine quantitative descriptions of rates of height and basic proportions of economic development of enterprise, volumes of productive resources, that an enterprise can use in a prospect for realization of the socio-economic program and development of material and technical base. Development of strategy of socio-economic development of enterprise will give an opportunity to get a maximal income from activity, to decrease unproductive charges, improve business reputation, create a positive climate in a collective and effective working command. Only a that enterprise can occupy high competition positions at the market, that understands clear and logical intercommunication between economic and social development, and also necessity of the strategic planning.
Strategy of socio-economic development of domestic enterprises is in modern terms of doing business
Keywords: підприємство; соціальний розвиток; економічний розвиток; стратегія соціально-еко- номічного розвитку; бізнес; enterprise; social development; economic development; strategy of socio-economic development; business